ANALISA BIAYA PELAKSANAAN ANTARA PELAT KONVENSIONAL DAN SISTEM PELAT MENGGUNAKAN METAL DECK - Widhiawati, I.A. Rai; Yana, A. A. G. A.; Asmara, A.A. (Jurnal Ilmiah Teknik Sipil, 2012)
The construction of concrete structure usually uses a conventional method where concrete mould and scaffolding used are made of wood. With the advance of technology there is an alternative developed to replace that method with the modern one. The slab structure constructed using metal deck is one example. The new method can provide a selection for entrepreneur of construction service to determine the correct method in constructing the slab in order to give the maximum result in term of cost and time aspects. To determine the construction method, the analyses of technique and cost of construction are needed. The analysis of construction technique is conducted for all network activities of works started from the work of scaffolding and concrete mould, reinforcement until casting. The unit price analysis is carried out for those works and more attention is paid to components affecting cost of material and labors. The unit price analysis used is a unit price analysis according to Indonesian standard, Standar Nasional Indonesia (SNI). The comparison is then conducted for cost analyses between conventional and metal deck slab cost of construction. Base on cost analysis results carried out on the building construction of Apartment of Le Grande Suites Pecatu, it is found that the cost of construction of 1st and 2nd floor using the conventional method and the metal deck construction are Rp. 962.710.088,91. and Rp. 890.380.917,53, respectively. The comparison results indicate that the work of the conventional slab with the volume of 142,85 m3 is more expensive than that of the metal deck slab with the volume of 121,99 m3, where the cost difference is equal to Rp 72.329.171,38 or 7,51%.
Keywords: conventional slab, metal deck slab, cost of construction